1985
DOI: 10.1677/joe.0.1040397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-hydroxytryptamine uptake blockers on the release of LH and prolactin in several different experimental steroid models in the rat

Abstract: The effect of the 5-hydroxytryptamine (5-HT) uptake blockers on the surges of LH and prolactin has been investigated in pro-oestrous rats and various experimental models used frequently to study the effects of steroids on LH and prolactin secretion in female rats. The steroid models were: rats ovariectomized on dioestrus, injected immediately with oestradiol benzoate (OB) and at 12.00 h on the next day (presumptive pro-oestrus) with progesterone (model 1); long-term ovariectomized rats injected with a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…The plasma concentrations of prolactin were measured using a double-antibody radioimmunoassay kit supplied by the NIADDK (Baltimore, MD, U.S.A.) as used in this laboratory by Horn & Fink (1985). Plasma concentrations of LH were measured by the ovine-ovine radioimmunoassay (Niswender, Midgley, Monroe & Reichert, 1968) as used in this laboratory (Horn & Fink, 1985). Plasma con¬ centrations of TSH were determined by doubleantibody radioimmunoassay using the kit supplied by the NIADDK and the results are expressed relative to the NIADDK rat TSH-RP-2 standard.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma concentrations of prolactin were measured using a double-antibody radioimmunoassay kit supplied by the NIADDK (Baltimore, MD, U.S.A.) as used in this laboratory by Horn & Fink (1985). Plasma concentrations of LH were measured by the ovine-ovine radioimmunoassay (Niswender, Midgley, Monroe & Reichert, 1968) as used in this laboratory (Horn & Fink, 1985). Plasma con¬ centrations of TSH were determined by doubleantibody radioimmunoassay using the kit supplied by the NIADDK and the results are expressed relative to the NIADDK rat TSH-RP-2 standard.…”
Section: Methodsmentioning
confidence: 99%
“…Animals used in this series of experiments were male and female COB Wistar rats ( 180-250 g) maintained as described by Horn & Fink (1985). The experimental models studied were: (i) the male rat; (ii) the prooestrous female rat; (iii) the short-term ovariectomized rat treated with 20 pg OB and 2 mg progesterone (model 1 ; Horn & Fink, 1985); (iv) the long-term ovari¬ ectomized female rat treated with 20 pg OB and 2 mg progesterone (model 2; Horn & Fink, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…The studies by Horn & Fink (1985) indicated that uptake blockade of 5-hydroxytryptamine (5-HT) can affect the release of luteinizing hormone (LH) and prolactin in pro-oestrous rats and in several different experimental animal models which have been used to study the effects of steroids on the release of LH and prolactin. The experiments reported in the present paper were carried out to determine whether the changes in hormone secretion did in fact reflect changes in 5-HT turnover in brain as indicated by the ratio of 5-hydroxyindoleacetic acid (5-HIAA)/5-HT (Tozer, Neff & Brodie, 1966).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations